Transmissive and transformative approaches to language teacher education - Jack C. Richards (Universitas Katolik Indonesia Atma Jaya, 2017)
In this paper I compare two contrasting educational philosophies that have had a significant impact on the way we approach and understand our practice as teacher educators. These have been labeled in several ways such as top-down versus bottom-up or product versus process based. I will characterize them a transmission-based approach and an ecological approach. My aim here is to describe and compare these two approaches and suggest how they offer complementary perspectives on the nature and practices of second language teacher education.